2008
DOI: 10.4028/www.scientific.net/kem.389-390.13
|View full text |Cite
|
Sign up to set email alerts
|

Study on Improvement of Material Removal Rate in Chemo-Mechanical Grinding (CMG) of Si Wafer

Abstract: Silicon wafer thinning process is meeting great challenges to fulfill requirements of ultra-thin IGBT for automotive applications. Chemo-mechanical grinding (CMG) process is potentially emerging stress relief thinning process which combines the advantages of fixed abrasive machining and chemical mechanical polishing (CMP). A major issue in CMG of Si wafers is the relatively low material removal rate (MRR). This paper studies the influence of the wheel specifications and grinding conditions on the MRR of CMG. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Ceria (CeO 2 ) was mainly chosen as an abrasive of the SAGW and has exhibited good performance in the silicon ultraprecision grinding. [20][21][22][23][24][25][26] Chemical reaction between CeO 2 abrasives and silicon during the grinding process was also studied. 26,27 However, few researchers investigated the grinding performance of SAGWs with different soft abrasives.…”
Section: Design Of Sagwmentioning
confidence: 99%
See 2 more Smart Citations
“…Ceria (CeO 2 ) was mainly chosen as an abrasive of the SAGW and has exhibited good performance in the silicon ultraprecision grinding. [20][21][22][23][24][25][26] Chemical reaction between CeO 2 abrasives and silicon during the grinding process was also studied. 26,27 However, few researchers investigated the grinding performance of SAGWs with different soft abrasives.…”
Section: Design Of Sagwmentioning
confidence: 99%
“…The problems include unstable grinding performance, low material removal rate (MRR), grinding burn, wafer surface scratches and so on. 24,25 This study builds upon the previous research on SAGW design. It optimizes design and formulation of the SAGW.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By effective use of chemically reactive abrasives, CMG offers better dimensional accuracy and similar surface integrity when comparing to CMP [5]. As a potential stress relief process subsequent to rapid grinding, CMG has been intensively studied to investigate the effects of wheel geometry and grinding condition on the removal rate [6], and effects of bond materials and additives on the surface quality [7] in our previous researches. The obtained results indicated that properly controlled pressure and heat were key to chemical reaction between abrasive and Si.…”
Section: Introductionmentioning
confidence: 99%